PENGARUH OMNICHANNEL CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION PADA PELANGGAN RITEL MODERN DI INDONESIA - Syamsuddin Syamsuddin; Asim Asim; Tri Gustanti; Utari Rahayu; Agus Agus; Ikramullah Ikramullah (Al-Buhuts, 2026)
This study aimed to examine the effect of omnichannel customer experience on customer satisfaction among modern retail customers in Indonesia. A quantitative approach was employed using an explanatory survey method and a cross-sectional design. Data were collected through an online questionnaire from 146 respondents selected using purposive sampling. Eligible respondents were at least 17 years old, had previously shopped at modern retailers, and had used at least two service channels provided by the same retailer. The instrument consisted of 18 items measured on a five-point Likert scale. Data were analyzed using simple linear regression. Because the residuals were non-normally distributed and heteroskedasticity was detected, statistical inference was strengthened using HC3 heteroskedasticity-robust standard errors and 5,000 bootstrap resamples. The results showed that omnichannel customer experience had a positive and significant effect on customer satisfaction (β = 0.728; p < 0.001), while the model explained 53.0% of the variance in customer satisfaction (R² = 0.530). The HC3 and bootstrap estimates confirmed the robustness of the findings. Theoretically, the findings supported Customer Experience Theory and Expectation Confirmation Theory. Practically, modern retail managers should integrate physical and digital channels consistently to enhance customer experience and satisfaction.